Analisis Karakteristik Briket Daun Jati dan Daun Jambu Mete - Arjuna, Muhamad; Kadir, Abd.; Barata, La Ode Ahmad (Teknik Mesin Universitas Halu Oleo, 2022)
Energy is something abstract that is difficult to prove but can be felt and has the ability to do work (energy is the capability for doing work). The purpose of this study was to determine the characteristics of Teak Leaves and Cashew Leaves Briquettes with varied compositions. The research method used is to analyze the characteristics of the flame temperature and compressive strength. Characteristic analysis of flame temperature and compressive strength was carried out with 3 variations of composition composition (70 teak leaves: 20 guava leaves: 10 clay, 50 teak leaves: 40 guava leaves: 10 clay, 20 teak leaves: 70 guava leaves: 10 clay) . From the results obtained, briquettes with a composition of 70% cashew leaves and 20% teak leaves with 10% clay adhesive are a good composition compared to other compositions with a temperature value of 233oC and a compressive strength value of 0.06272 N/mm2.Keywords: Briquettes, teak leaves, and cashew leaves